2023
DOI: 10.1002/anie.202215778
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Artificial Membraneless Organelles in Saccharomyces cerevisiae To Enhance Chemical Production

Abstract: Microbial cell factories provide a green and sustainable opportunity to produce value-added products from renewable feedstock. However, the leakage of toxic or volatile intermediates decreases the efficiency of microbial cell factories. In this study, membraneless organelles (MLOs) were reconstructed in Saccharomyces cerevisiae by the disordered protein sequence A-IDPs. A regulation system was designed to spatiotemporally regulate the size and rigidity of MLOs. Manipulating the MLO size of strain ZP03-FM, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…86,102 It has also been reported that regulating the size and rigidity of synthetic MOLs in Saccharomyces cerevisiae can increase methanol assimilation efficiency and the titer and yield of n-butanol. 103 The combination of protein scaffolds, ligands, lysis, or capacitive proteins and photosensitive proteins to improve the manipulability of ASCs based on LLPS will create considerable prospects for the application of intracellular compartments in MCFs.…”
Section: Design Of Artificial Subcellular Compartmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…86,102 It has also been reported that regulating the size and rigidity of synthetic MOLs in Saccharomyces cerevisiae can increase methanol assimilation efficiency and the titer and yield of n-butanol. 103 The combination of protein scaffolds, ligands, lysis, or capacitive proteins and photosensitive proteins to improve the manipulability of ASCs based on LLPS will create considerable prospects for the application of intracellular compartments in MCFs.…”
Section: Design Of Artificial Subcellular Compartmentsmentioning
confidence: 99%
“…Although the condensation process and degree of spontaneous aggregation of synthetic MOLs cannot be perfectly controlled, recent studies have reported that the aggregation of protein condensates is affected by protein concentration, external membrane environment strength, the presence of RNA, the number of tyrosine–arginine (Y-R) pairs, positive charge, and other factors. , It has also been reported that regulating the size and rigidity of synthetic MOLs in Saccharomyces cerevisiae can increase methanol assimilation efficiency and the titer and yield of n -butanol . The combination of protein scaffolds, ligands, lysis, or capacitive proteins and photosensitive proteins to improve the manipulability of ASCs based on LLPS will create considerable prospects for the application of intracellular compartments in MCFs.…”
Section: Designing Artificial Subcellular Compartments To Enhance The...mentioning
confidence: 99%
“…PpID-based functionalization of synthetic condensates thus provides the basis for the continued adoption of membraneless organelles as hubs for synthetic biology 6,23,24 . In particular, recruiting metabolic pathways to condensates can divert flux of intermediates away from competing pathways [30][31][32][33][34] . Indeed, the relative stoichiometry and degree of recruitment of enzymes can significantly impact the resulting product formation 56 .…”
Section: Ppids Enable Stoichiometric Control Of Multiple Cargo In a C...mentioning
confidence: 99%
“…For example, we previously introduced the Corelet system, whereby weakly interacting protein domains optogenetically multimerize on spherical protein assemblies of human ferritin, resulting in spatiotemporally tunable phase separation 40 . Others have added interaction domains to recruit various proteins to functionalize related synthetic organelles 26,27,33,34 . However, previous efforts to systematically engineer biomolecular condensates fall short of providing a quantitative framework for controlling the recruitment of various functional proteins into the condensates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to overcome the carbon loss in acetyl-CoA synthesis, 2023) also introduced the GATHCYC pathway along with other genetic engineering modifications into a n-butanol producing S. cerevisiae strain that showed an increase in the acetyl-CoA supply that improved the n-butanol titer up to 1.75 g/L with a decrease of 35.2% of the total CO 2 (Zhou et al, 2023).…”
Section: Avoiding Unnecessary Decarboxylationmentioning
confidence: 99%